Freeze-Drying Technology in Foods - Prosapio, Valentina; Lopez-Quiroga, Estefania (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This Special Issue provides an update on the most recent research and developments in the area of freeze-drying technology in foods. It presents a combination of experimental and modeling studies, offering an overview of oncoming challenges and opportunities on the topic.